Identification of implementation enhancement strategies for national comprehensive care standards using the CFIR-ERIC approach: a qualitative study - Beibei Xiong; Daniel X. Bailey; Christine Stirling; Paul Prudon; Melinda Martin-Khan (BMC, 2024)
Abstract Background Comprehensive care is important for ensuring patients receive coordinated delivery of healthcare that aligns with their needs and preferences. While comprehensive care programs are recognised as beneficial, optimal implementation strategies in the real world remain unclear. This study utilises existing implementation theory to investigate barriers and enablers to implementing the Australian National Safety and Quality Health Service Standard 5 - Comprehensive Care Standard in acute care hospitals. The aim is to develop implementation enhancement strategies for work with comprehensive care standards in acute care. Methods Free text data from 256 survey participants, who were care professionals working in acute care hospitals across Australia, were coded using the Consolidated Framework for Implementation Research (CFIR) using deductive content analysis. Codes were then converted to barrier and enabler statements and themes using inductive theme analysis approach. Subsequently, CFIR barriers and enablers were mapped to the Expert Recommendations for Implementing Change (ERIC) using the CFIR-ERIC Matching Tool, facilitating the development of implementation enhancement strategies. Results Twelve (n = 12) CFIR barriers and 10 enablers were identified, with 14 barrier statements condensed into 12 themes and 11 enabler statements streamlined into 10 themes. Common themes of barriers include impact of COVID-19 pandemic; heavy workload; staff shortage, lack of skilled staff and high staff turnover; poorly integrated documentation system; staff lacking availability, capability, and motivation; lack of resources; lack of education and training; culture of nursing dependency; competing priorities; absence of tailored straties; insufficient planning and adjustment; and lack of multidisciplinary collaboration. Common themes of enablers include leadership from CCS committees and working groups; integrated documentation systems; established communication channels; access to education, training and information; available resources; culture of patient-centeredness; consumer representation on committees and working groups; engaging consumers in implementation and in care planning and delivery; implementing changes incrementally with a well-defined plan; and regularly collecting and discussing feedback. Following the mapping of CFIR enablers and barriers to the ERIC tool, 15 enhancement strategies were identified. Conclusion This study identified barriers, enablers, and recommended strategies associated with implementing a national standard for comprehensive care in Australian acute care hospitals. Understanding and addressing these challenges and strategies is not only crucial for the Australian healthcare landscape but also holds significance for the broader international community that is striving to advance comprehensive care.